2011
DOI: 10.1037/a0021439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manifest ethnic identification on employment discrimination.

Abstract: Evidence from recent laboratory experiments suggests that ethnic identification can lead to negative evaluations of ethnic minorities (Kaiser & Pratt-Hyatt, 2009). The current research considers the generalizability of these findings to face-to-face interactions in contexts wherein impression management concerns are salient: the workplace hiring process. In a field experiment, Black, Hispanic, and Irish individuals applied for retail jobs with or without visible display of their ethnic identification. Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…Yet the measure can be criticized for not targeting groups specifically and, indeed, other research has developed measures to assess identification with particular racial and ethnic groups (e.g., Knowles & Peng, 2005; Sellers, Rowley, Chavous, Shelton, & Smith, 1997). Previous investigators have even manipulated the outward expression of an interaction partner’s identification with a specific ethnic group by having confederates wear hats with slogans about ethnic pride (e.g., Barron, Hebl, & King, 2011). Despite the benefits of these alternate approaches to studying ethnic identification, using the MEIM in the present research allowed us to test both actor and partner effects in interactions between different ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Yet the measure can be criticized for not targeting groups specifically and, indeed, other research has developed measures to assess identification with particular racial and ethnic groups (e.g., Knowles & Peng, 2005; Sellers, Rowley, Chavous, Shelton, & Smith, 1997). Previous investigators have even manipulated the outward expression of an interaction partner’s identification with a specific ethnic group by having confederates wear hats with slogans about ethnic pride (e.g., Barron, Hebl, & King, 2011). Despite the benefits of these alternate approaches to studying ethnic identification, using the MEIM in the present research allowed us to test both actor and partner effects in interactions between different ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Barron et al (2011) did not disentangle nonverbal and verbal behavior from each other. That is, the managers' interactions were coded on interpersonal aspects from the entire interaction, encompassing both nonverbal and verbal behaviors.…”
Section: Discussionmentioning
confidence: 97%
“…Barron, King, and Hebl (2011) sent strongly and weakly identified racial minorities into retail stores to apply for jobs. Identification was communicated with the applicants' hats, which contained logos expressing strong identification (e.g., ''Black and Proud'') or neutral content.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a field experiment on the hiring process, Barron et al (Barron et al, 2011) found that store personnel exhibited greater positivity and engaged in longer interactions when they were randomly assigned to minority applicants who displayed prominently their ethnic identification. This observation contradicts an earlier laboratory finding that high identification leads to negative evaluation of ethnic minorities (Kaiser and Pratt-Hyatt, 2009).…”
Section: Intellectual Backgroundmentioning
confidence: 99%